Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3928/00989134-20121003-05
|View full text |Cite
|
Sign up to set email alerts
|

Pay Attention!: The Critical Importance of Assessing Attention in Older Adults with Dementia

Abstract: Attention is an important cognitive domain that is affected in Alzheimer’s disease and other dementias. It influences performance in most other cognitive domains, as well as activities of daily living. Nurses are often unaware of the critical importance of assessing attention as part of the overall mental status examination. This article addresses an important gap in nurses’ knowledge. The authors present a brief overview of attention as a critical cognitive domain in dementia; review instruments/methods for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…As one of the most prominent behavioral symptoms in AD, cognitive impairment is also associated with apathy [45][46][47]. While memory impairment is common in AD, attention [48] and executive dysfunction [49], such as planning, spatial navigation attention [50][51][52] and verbal fluency [53] are also particularly noted to be impaired as the disease progresses to later stages, which is particularly relevant to our sample which is more impaired. However, it is important to differentiate between the DAS Executive apathy items and executive functioning assessments, wherein the overt, observational assessments of the former and the performance-based assessment of the latter, are unlikely to fully overlap but are more likely to measure similar elements relating to demotivation towards planning, organization and attention.…”
Section: Discussionmentioning
confidence: 69%
“…As one of the most prominent behavioral symptoms in AD, cognitive impairment is also associated with apathy [45][46][47]. While memory impairment is common in AD, attention [48] and executive dysfunction [49], such as planning, spatial navigation attention [50][51][52] and verbal fluency [53] are also particularly noted to be impaired as the disease progresses to later stages, which is particularly relevant to our sample which is more impaired. However, it is important to differentiate between the DAS Executive apathy items and executive functioning assessments, wherein the overt, observational assessments of the former and the performance-based assessment of the latter, are unlikely to fully overlap but are more likely to measure similar elements relating to demotivation towards planning, organization and attention.…”
Section: Discussionmentioning
confidence: 69%
“…As mentioned earlier, deficits in sustained attention occur in the late stages of AD, but performance on more complex attentional functions is impaired earlier in the disease 27. Some studies have used the MOTYB to distinguish stages of AD,53 54 including one small study which showed that the predictive value of the MMSE for dementia could be augmented by the addition of the MOTYB 53.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing nurse tasks or responsibilities for delirium care means that they must be given the time, resources, and support from institutional leadership, including unit and executive leadership. Another solution to the time barrier is to integrate the work of detection and management as closely as possible into the current context of care and break it into manageable chunks, for instance having a nurse assess attention as part of the initial shift assessment can take as little as 30 seconds (Kolanowski et al, 2012). These solutions must be part of the usual workflow and may be more easily accepted if it does not become an additional workload issue.…”
Section: Discussionmentioning
confidence: 99%